Identification of Acetate-oxidizing Bacteria in the UASB Applied to Low Temperature Treatment of Deicing Fluid Wastewater - YAMAGUCHI, Takashi; ARAKI, Nobuo; NAGANO, Akihiro; IMAI, Takahiro (ENVIRONMENTAL ENGINEERING RESEARCH, 2006)
Anaerobic acetate-oxidizing bacteria were identified in the up-flow anaerobic sludge blanket reactor (UASB) applied to the low temperature treatment of sulfate-added wastewater of deicing fluid. Clone library analysis of PCR-amplified 16S ribosomal DNA was employed to identify bacteria, in which acetate was supplied as an electron donor. Identified clones were dominated by those derived from Citrobacter freundii and Desulfomicrobium baculatum in the enrichment culture incubated at 10°C, and those from Clostridium celerecrescens and Desulfovibrio sp. in the enrichment culture incubated at 30°C. Almost all of the cells were detected by FISH analysis using only two kinds of probes specific for hydrogen-utilizing sulfate-reducing bacteria and for either Citrobacter freundii or Clostridium celerecrescens in the both enrichment culture. Those two kinds of bacteria could be an acetate-oxidizing member in each culture. FISH analysis revealed that Citrobacter freundii, Clostridium celerecrescens and hydrogen-utilizing sulfate-reducing bacteria actually existed in the UASB, and the ratio of them to DAPI-stained total cells were about 2%, 3% and 6%, respectively.